Language Acquisition and Function of Preschool-Aged Inclusive Children in Mataram City - Wahyuni, Wika; Agustina, Hani (JUPE : Jurnal Pendidikan Mandala, 2025)
This study aims to describe language acquisition and language functions in preschool-aged inclusive children in Mataram City. The research was conducted at two schools, namely Kindy House (a private school) and SLB Negeri 1 Mataram (a public special school). The focus of the study is directed toward the stages of language acquisition and the language functions that emerge in children’s interactions within the school environment. This study employs a descriptive qualitative approach, with data collected through observation, utterance recording, and interviews with teachers. The research subjects consist of preschool-aged inclusive children ranging from 3 to 6 years old, representing three main characteristics: children with Attention Deficit Hyperactivity Disorder (ADHD), Autism Spectrum Disorder (ASD), and Down Syndrome (DS). Data analysis was conducted by classifying children’s language data based on stages of language acquisition and language functions according to Halliday’s theory. The results indicate that language acquisition among inclusive children occurs at varying stages and does not always align with their chronological age. The dominant language functions observed include instrumental, regulatory, and interactional functions, while representational functions remain limited to some subjects. These findings suggest that mapping language acquisition and language functions can serve as an initial basis for identifying the linguistic profiles of preschool-aged inclusive children, particularly for preschool teachers and parents